Depression and risk of suicide in the hospital environment: a focus on nursing professionals (Research, Society and Development, 2022)
Depression and suicide are complex phenomena that bring intense suffering to the lives of affected people, their families, friends and community. These two phenomena coexist and influence each other, and both are considered significant public health problems. This study aimed to describe, through scientific articles, depression and the risk of suicide in the hospital environment, focusing on nursing professionals. This is an integrative literature review, carried out between May and September 2021, using publications indexed in the electronic database: Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), Nursing Database (BDENF) and National Library of Medicine, USA (PubMed). Thus, it is understood that the risk of suicide was effectively and expressively correlated with depression. And that nurses are at high risk for suicide. In this study, it was possible to identify that depression and suicide are a serious public health problem that is continually worsening, requiring the development of more in-depth studies, research and care strategies to help prevent them.